SPECIFIC DETECTION OF Salmonella spp. WITH MOLECULAR BIOLOGICAL TECHNIQUES - Marija TRKOV; G. AVGUŠTIN (Acta Agriculturae Slovenica)
A method for specific detection of Salmonella spp. was developed based on 16S rRNA targeted PCR (polymerase chain reaction). A method based on recognition of specific region of 16S rRNA gene was published previously by Lin and Tsen in 1996. The sequence analysis of recently determined small subunit ribosomal genes from Salmonella spp. showed however, that the 16SF1 and 16SIII primers are not suitable for specific amplification of all Salmonella strains. 16SF1 was modified and a new forward PCR primer was designed. The specificity of the method was tested using 87 Salmonella strains and 30 non-Salmonella strains of the family Enterobacteriaceae and compared with two other previously published methods and found to be 100% specific. The reverse primer was also labelled with a tetramethylrhodamine isothyiocianate fluorescent dye and successfully used as a probe in in situ experiments.